Case Report: Extended cardiopulmonary resuscitation in sudden cardiac arrest after acute myocardial infarction - Yu, Zhongkai; Hu, Yubin; Chen, Xiuli (Frontiers in Cardiovascular Medicine, 2024)
Out-of-hospital cardiac arrest (OHCA) mostly occurs in crowded public places outside hospitals, such as public sports facilities, airports, railway stations, subway stations, and shopping malls. The emergency department of Liaocheng People's Hospital in Shandong Province admitted one patient with OHCA in August 2021, who suddenly suffered a loss of consciousness and cardiac arrest during exercise after dinner. Witnesses immediately gave continuous chest compressions and artificial respiration and called our hospital's emergency department (at 120). Arriving at the emergency department, we continued to provide chest compressions and ventilator-assisted ventilation after performing endotracheal intubation. We administered adrenaline for cardiac excitation, dopamine for maintained blood pressure, sodium bicarbonate to correct the acidosis, and multiple electric defibrillations. However, the patient's cardiac Doppler ultrasound indicated poor cardiac contractions, and extracorporeal membrane oxygenation (ECMO) was started immediately. We performed coronary angiography for the patient with ECMO support, indicating that the patient had an 80% critical stenosis of the left main coronary artery and an 80%–90% stenosis in the middle section of the left anterior descending artery with an aneurysm. Fortunately, there was no obvious stenosis in the right coronary artery. The patient was transferred to the intensive care unit and received comprehensive treatment, including anticoagulation, myocardial nutritional support, improvement of cardiac function, continuous renal replacement therapy, organ function protection, anti-inflammatory treatment, and rehabilitation. Coronary artery bypass grafting was performed after the patient's condition stabilized, and he was finally discharged. ECMO support therapy for patients with cardiac arrest can be considered when economic conditions permit. It is very important to conduct the necessary examinations in the early stage of resuscitation with ECMO support to clarify the cause of the cardiac arrest and to treat it accordingly.